The Governance of Resilience. How the Health Systems Have Coped with The Covid-19 Pandemic - Guido Giarelli (Culture e Studi del Sociale, 2020)
After considering the reasons why pandemics are destined to remain also in the near future in our late industrial societies, a conceptual framework for the analysis of governance of resilience of health systems is described and then applied in details following its main four dimensions to the ways various health systems have coped with the pandemic of COVID-19, with specific reference to the Italian National Health Service. In the conclusions, an overall assessment of the ways in which the health systems have responded to the pandemic of COVID-19 is traced on the basis of three different levels of resilience governance and their implications.